Respiratory and Rehabilitation Expert Consensus on Full-cycle Rehabilitation Assessment and Treatment for Elderly Patients with Chronic Obstructive Pulmonary Disease - CHEN Xin; JIA Jie; DING Yipeng; YE Xujun; DONG Anqin; HE Jing; LIAO Weijing; ZHENG Jieqiao; YU Binbin; CHEN Zuobing; FANG Yuan; YAO Liqing; et al. (康复学报)
Chronic obstructive pulmonary disease (COPD) is one of the major chronic airway diseases, with the highest prevalence among individuals over 60 years old, significantly impacting the health of elderly patients. Both domestic and international COPD prevention and treatment guidelines recommend pulmonary rehabilitation as a complementary and effective adjunct to pharmacological treatment. Pulmonary rehabilitation can significantly improve patients' respiratory function and physical fitness, alleviate symptoms, and reduce hospitalization and mortality rates. However, the specific contents of pulmonary rehabilitation for elderly COPD patients differ depending on the stage of the disease. This expert consensus elaborates on the assessment and treatment contents of pulmonary rehabilitation for elderly COPD patients in the acute exacerbation period, acute exacerbation remission period, and outpatient stable period, aiming to provide guidance for pulmonary rehabilitation treatment at different stages of the disease. This consensus identifies common functional impairments in elderly COPD patients, including respiratory dysfunction, exercise tolerance impairment, psychological issues, swallowing dysfunction and cognitive impairment. It recommends a comprehensive assessment of elderly COPD patients' multifaceted impairments based on the International Classification of Functioning, Disability, and Health (ICF) framework, covering four aspects：body structure, body function (respiratory function, cardiac function, exercise function, psychological and cognitive function, swallowing function, and nutritional factors), activity and participation, and environmental factors. Pulmonary rehabilitation is suitable for all patients exhibiting relevant symptoms and/or those at high risk of acute exacerbations (high-level evidence). As the disease progresses, the rehabilitation team, treatment plan, and treatment location should be adjusted in a timely manner, forming a continuous rehabilitation cycle. Smoking cessation is a crucial intervention to slow down the decline in lung function and the progression of COPD (high-level evidence). Through adequate nutritional support, elderly COPD patients can improve their nutritional status, enhance physical strength and quality of life, better manage the disease, and promote rehabilitation (low to moderate-level evidence). Oxygen therapy is recommended for patients with advanced COPD who remain hypoxemic at rest (low to moderate-level evidence). Some emerging rehabilitation treatments (such as neuromuscular electrical stimulation, acupuncture, and certain traditional Chinese medicines) may have some value for elderly COPD patients (low to moderate-level evidence. This expert consensus divides rehabilitation treatment into three stages：Phase I Pulmonary Rehabilitation, Phase II Pulmonary Rehabilitation, and Phase III Pulmonary Rehabilitation, based on the different stages of elderly COPD patients. It further details the target population, implementation location, rehabilitation content, assessment content, participating disciplines, and rehabilitation goals for each stage, emphasizing the need for clinical respiratory specialists, primary care physicians, rehabilitation physicians/therapists, nurses, nutritionists, psychologists, and social workers to actively coordinate and collaborate throughout the full-cycle rehabilitation process for elderly COPD patients.